Kwantyfikacja cech społecznych - Ostasiewicz, Walenty (Quantification of social features, 2006)
The modem measurement theory which began in 1901 with Holder, and culminated with monograph by Krantz D.H., Luce R.D., Suppes P. and Tversky A. is of a little use in social and behavioral sciences. In the paper there are discussed some shortcomings of this theory, and indicated some new developments appropriate for scaling in social sciences. Particularly, the theory proposed by D. Bartholomew seems to have a good perspective for wide applications. This theory is shortly highlighted.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1142, s. 167-173